A facile strategy for tailoring polyaniline by MoS2 nanosheets to obtain excellent electrochemical properties. (10th May 2021) - Dai, Juguo; Zeng, Shanni; Lv, Yan; Xie, Hongmei; Luo, Lili; Xu, Yiting; Dai, Lizong
Abstract: In this paper, the morphology and phase structure of MoS2 /PANI (MP) composites are rational designed, with PANI interwoven into the gap of MoS2 to form a three-dimensional heterostructure via one-step hydrothermal method. The strong interaction between two components results in an increase of the interlayer spacing of MoS2 by about 0.32 nm, which provides more channels for rapid charge transport and ionic diffusion. Consequently, the MP composites deliver high specific capacitance (756.2 F g − 1 at 1 A g − 1 ) and long cycling stability (78.1% capacitance retention after 5000 cycles) in three-electrode systems. When assembled into asymmetric supercapacitor devices, the resultant devices also have high specific capacitance (521.7 F g − 1 at 1 A g − 1 ), remarkable cycling stability (94.7% capacitance retention after 10, 000 cycles), high coulombic efficiency (97.7%) and superior energy density (46.4 Wh kg −1 at the power density of 400 W kg −1 ). Furthermore, theoretical calculation verifies that the contribution of each component to the electrochemical performance of MP composites, which provides a new idea for the design of active components proportion. We hope that this study will spark extensive interests in the exploration of novel practical energy-storage devices.